2015
DOI: 10.15171/ijoem.2015.565
|View full text |Cite
|
Sign up to set email alerts
|

Working and Living in Northern vs Southern Ontario Is Associated with the Duration of Compensated Time off Work: A Retrospective Cohort Study

Abstract: The disability duration in northern Ontario is longer than that in southern Ontario. Future research should focus on assessing the relevant factors associated with this observation to identify opportunities for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…22 Although cohort restrictions resulted in the exclusion of many claims, this study was able to retain more claims than were retained in previous research using both residential and employer location data. 19 This study was able to apply a matching algorithm to reduce the bias of estimated differences in RTW of mobile workers similar to that in existing studies. 11,13 What also separates this study from the aforementioned studies is the ability to analyze an outcome based on calendar RTW data as opposed to simply compensated temporary total or partial days paid.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
See 4 more Smart Citations
“…22 Although cohort restrictions resulted in the exclusion of many claims, this study was able to retain more claims than were retained in previous research using both residential and employer location data. 19 This study was able to apply a matching algorithm to reduce the bias of estimated differences in RTW of mobile workers similar to that in existing studies. 11,13 What also separates this study from the aforementioned studies is the ability to analyze an outcome based on calendar RTW data as opposed to simply compensated temporary total or partial days paid.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…The only other study that uses both residential and employer location data found that workers who worked in a different region of the province of Ontario than their region of residence had a lower likelihood of transitioning off disability benefits than those working and residing in the same region of Ontario. 19 In the present study, contrasts are drawn between the work disability duration of nonmobile and intraprovincially and interprovincially mobile workers. Similar to the findings from research on interjurisdictionally mobile workers, 12,13 interprovincially mobile workers had the longest work disability duration.…”
Section: Interpretation Of Findingsmentioning
confidence: 86%
See 3 more Smart Citations